Implementasi Konsep Pengentasan Kemiskinan Dalam Perspektif Islam di Bank Wakaf Mikro Mawaridussalam - Reza Mahendra; Abdul Hadi Ismail (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine the implementation of the concept of poverty in an Islamic perspective at the Mawaridussalam Micro Waqf Bank. This study uses a qualitative descriptive method to describe and describe data in the form of sentences or paragraphs clearly and in detail. Sources of data in this study were obtained from the managers and customers of the Mawaridussalam Micro Waqf Bank. The data collected is data related to the concept of poverty alleviation in an Islamic perspective applied by the Mawaridussalam Micro Waqf Bank. The data collection method used is the method of observation, interviews, and documentation. The data that has been collected will be analyzed by editing, organizing, and analyzing methods. The results of the study show that the Mawaridussalam Micro Waqf Bank has two programs, namely financial assistance and mentoring. In managing the funds, the Mawaridussalam Micro Waqf Bank uses a regulated management scheme, namely funds worth IDR 4,000,000,000.00- distributed by LAZNAS BSM and then divided into IDR 3,000,000,000.00- as endowment funds deposited at Bank Syariah Indonesia and The proceeds from the deposit are used as administrative costs for the Mawaridussalam Micro Waqf Bank. Meanwhile, IDR 1,000,000,000.00 is used as funds to be distributed to customers according to a pre-arranged scheme. In poverty alleviation, the Mawaridussalam Micro Waqf Bank implements its program as a poverty alleviation concept that is in accordance with an Islamic perspective, namely providing financial assistance without usury or collateral and three pillars of assistance in the form of religious assistance materials, business development, and family management.